mwr Xer site-specific recombination is hypersensitive to DNA supercoiling. - Trigueros, S; Tran, T; Sorto, N; Newmark, J; Colloms, S; Sherratt, D; Tolmasky, M (2009)
The multiresistance plasmid pJHCMW1, first identified in a Klebsiella pneumoniae strain isolated from a neonate with meningitis, includes a Xer recombination site, mwr, with unique characteristics. Efficiency of resolution of mwr-containing plasmid dimers is strongly dependent on the osmotic pressure of the growth medium. An increase in supercoiling density of plasmid DNA was observed as the osmotic pressure of the growth culture decreased. Reporter plasmids containing directly repeated mwr, or the related cer sites were used to test if DNA topological changes were correlated with significant changes in efficiency of Xer recombination. Quantification of Holliday junctions showed that while recombination at cer was efficient at all levels of negative supercoiling, recombination at mwr became markedly less efficient as the level of supercoiling was reduced. These results support a model in which modifications at the level of supercoiling density caused by changes in the osmotic pressure of the culture medium affects resolution of mwr-containing plasmid dimers, a property that separates mwr from other Xer recombination target sites.